2015
DOI: 10.1007/s00784-015-1528-y
|View full text |Cite
|
Sign up to set email alerts
|

PRGF exerts a cytoprotective role in zoledronic acid-treated oral cells

Abstract: At present, there is no definitive treatment for bisphosphonates-related osteonecrosis of the jaw (BRONJ), being mainly palliatives. Our results revealed that PRGF has a cytoprotective role in cells exposed to zoledronic acid, thus providing a reliable adjunctive therapy for the treatment of BRONJ pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
1
12
0
2
Order By: Relevance
“…With regards to the evaluation of cytotoxic potential, the results of the present study highlighted the difference in effect between the novel synthesized compounds and ZA: All three novel molecules were able to restore HGF membranes integrity, which is compromised following LPS treatment; but membrane integrity still appeared damaged when the HGFs were exposed to ZA. This evidence is not surprising, as our group had reported it in previous studies (23,32), and it was also reported in several other papers (33,34) which clearly underline the ZA toxicity on a fibroblast population.…”
Section: Discussionsupporting
confidence: 82%
“…With regards to the evaluation of cytotoxic potential, the results of the present study highlighted the difference in effect between the novel synthesized compounds and ZA: All three novel molecules were able to restore HGF membranes integrity, which is compromised following LPS treatment; but membrane integrity still appeared damaged when the HGFs were exposed to ZA. This evidence is not surprising, as our group had reported it in previous studies (23,32), and it was also reported in several other papers (33,34) which clearly underline the ZA toxicity on a fibroblast population.…”
Section: Discussionsupporting
confidence: 82%
“…Among the growth factors, PRGF, has demonstrated the potential to influence bone regeneration and promote osteogenic differentiation in a wide number of surgical applications in the oral field ( Pardinas Lopez et al, 2015 ; Del Fabbro et al, 2015 ; Adornato et al, 2007 ; Martins et al, 2012 ; Anitua et al, 2013 ; Khouly et al, 2017 ; Anitua et al, 2009 ; Del Fabbro et al, 2013 ; Anitua et al, 2015 ). Moreover, it has been reported that PRGF acts as a cytoprotector against the toxic effect of bisphosphonates on fibroblasts and osteoblasts ( Anitua et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The quantification of type I collagen was performed by Western blot. At day 7, total protein was extracted and Western blot analysis was performed as previously described . The blots were incubated with primary antibody against type I collagen (Santa Cruz Biotechnology, Heidelberg, Germany) overnight at 4°C and with the secondary antibody (horseradish peroxidase‐conjugated goat anti‐mouse) (Santa Cruz Biotechnology) for 1 hour at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…At day 7, total protein was extracted and Western blot analysis was performed as previously described. 20 The blots were incubated with primary antibody against type I collagen (Santa Cruz Biotechnology, Heidelberg, Germany) overnight at 4°C and with the secondary antibody (horseradish peroxidase-conjugated goat anti-mouse) (Santa Cruz Biotechnology) for 1 hour at room temperature. Blots were then developed by chemiluminescence with Supersignal West Pico substrate (Thermo Scientific-Pierce Biotechnology, Rockford, IL, USA) using an image analyzer (Chemidoc image analyzer, Bio-Rad Laboratories, Hercules, CA, USA).…”
Section: Type I Collagen Biosynthesismentioning
confidence: 99%